Deterministic and Stochastic Dynamics of an Eco-epidemiological Model - B. N. R. Karuna; K. Lakshmi Narayan; B. Ravindra Reddy (International Journal of Mathematics And its Applications, 2017)
A three-compartmental eco-epidemiological model consisting of three species, namely, the susceptible prey, the infected prey and the predator population is considered. The SIR type deterministic epidemiological models are revisited and stochastic modeling for those models is introduced. The exponential and mean square stability for the stochastic model is derived and the considerable discrepancy between the results of stochastic and deterministic models is supported by numerical simulations with a hypothetical set of data.